2019
DOI: 10.1111/jcmm.14666
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of the novel marine oxygen carrier M101 during cold preservation of rat and human pancreas

Abstract: Ischaemia impairs organ quality during preservation in a time‐dependent manner, due to a lack of oxygen supply. Its impact on pancreas and islet transplantation outcome has been demonstrated by a correlation between cold ischaemia time and poor islet isolation efficiency. Our goal in the present study was to improve pancreas and islet quality using a novel natural oxygen carrier (M101, 2 g/L), which has been proven safe and efficient in other clinical applications, including kidney transplantation, and for sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 57 publications
(97 reference statements)
1
23
0
3
Order By: Relevance
“…Direct oxygenation of damaged tissue is a therapeutic strategy paving way for the use of oxygen carriers such as M101. Indeed, preservation and perfusion of rat and human pancreas (ex vivo) 32 and porcine kidneys (in vivo) 33 with M101 solution improved graft function and transplantation outcome. Interestingly, first M101 use in human clinical trial demonstrated that kidney preservation with M101 solution (1 g/L) before transplantation, improved graft survival and renal function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Direct oxygenation of damaged tissue is a therapeutic strategy paving way for the use of oxygen carriers such as M101. Indeed, preservation and perfusion of rat and human pancreas (ex vivo) 32 and porcine kidneys (in vivo) 33 with M101 solution improved graft function and transplantation outcome. Interestingly, first M101 use in human clinical trial demonstrated that kidney preservation with M101 solution (1 g/L) before transplantation, improved graft survival and renal function.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to this exceptional O 2 -binding capacity, M101 releases O 2 according to a simple gradient and possesses antioxidative properties. It also exhibits intrinsic superoxide dismutase (SOD)-like activity, preventing the occurrence of potentially harmful hemoglobin degradation products such as heme-protein-associated free radical species (ROS), or ROS related to ischemia in the solution 31 , 32 . These desirable properties of M101 open new vistas for its wide industrial and therapeutic applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the size of this molecule is 250 times smaller than a human red blood cell, allowing it to diffuse in all areas of the microcirculation, without diffusing outside the vascular sector. This product has been the subject of numerous publications [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] . This worm is farmed in aquaculture in a very strict good manufacturer practice conditions under ISO-13485 regulation.…”
Section: Evaluation Of the Hypothesismentioning
confidence: 99%
“…12 Similar results were reported in preclinical models of lung, heart, and pancreas graft preservation. [13][14][15][16] Recently, in a French clinical trial using kidney transplantation from deceased donors, M101 demonstrated safety and efficacy, drastically decreasing the rate of delayed graft function recovery from 26% to 7%. 17 However, M101 performance in cold-stored liver graft remains to be studied.…”
Section: Introductionmentioning
confidence: 99%